Theoretical study of a high-efficiency GaP–Si heterojunction betavoltaic cell compared with metal–Si Schottky barrier betavoltaic cell - Yu Wang; Jingbin Lu; Renzhou Zheng; Xiaoyi Li; Yumin Liu; Xue Zhang; Yuehui Zhang; Ziyi Chen (AIP Advances, 2021)
In this work, energy converters, which contain a GaP–Si heterojunction and Si-based Schottky barrier diodes with Al, Ti, Ag, and W, are used to convert 2 μm-thick 63Ni radioactive source energy into electrical energy. First, energy deposition distributions of the 63Ni radioactive source in these converters are simulated by using the Monte Carlo method. Then, the electrical output properties of the 63Ni/GaP–Si cell and 63Ni/metal–Si cell are determined through the numerical calculation. For the 63Ni/GaP–Si cell, with the optimized thickness of the GaP layer and doping concentration of Si, the maximum output power density and the conversion efficiency are 0.189 µW cm−2 and 1.83%, respectively. For the Si-based Schottky barrier cells with Al, Ti, Ag, and W, the 63Ni/Al–Si cell has the best electrical output properties with the same thickness of the metal layer and doping concentration of Si. When the thickness of metal Al is 0.1 µm and the doping concentration Na is 1 × 1013 cm−3, the maximum output power density and the conversion efficiency are 0.121 µW cm−2 and 1.18%, respectively. The calculation results indicate that the 63Ni/GaP–Si battery has better electrical output properties than the 63Ni/Al–Si Schottky battery. These results are valuable for fabricating practical batteries.